The racial issue in the academic output of social work - Ford, Juliana Viana; Pedroso, Gustavo José de Toledo; Garcia, Fernanda Andrade (Argumentum, 2022)
This article discusses the relationship between the racial issue and the production of academic knowledge in Brazilian social work. It is the result of bibliographical research and aims to provoke and deepen reflections on how the racial issue reverberates within the intellectual output of social work. The text consists of two parts: in the first, the conditions for the existence of the idea of race and the supposed universality of academic knowledge under the process of capitalist expansion are demonstrated. The second part is a questioning of the incorporation of the racial issue into the production of knowledge in social work, based on some considerations regarding the expansion of graduate courses in the 1970s and the process of reformulation of fundamentals and of the professional profile in the 1980s.